7
$\begingroup$

How would you solve the following

$$\int^1_0 \frac{\operatorname{Li}_3(x)}{1-x} \log(x)\, \mathrm dx$$

I might be able to relate the integral to Euler sums .

$\endgroup$
6
$\begingroup$

A related problem. You can have the following closed form

$$\int^1_0 \frac{\operatorname{Li}_3(x)}{1-x} \log(x)\, dx= -\sum _{k=1}^{\infty }{\frac {\psi' \left( k+1 \right) }{{k}^{3}}}\sim -0.7115661976, $$

where $\psi(x)$ is the digamma function.

Another possible solution:

$$\int^1_0 \frac{\operatorname{Li}_3(x)}{1-x} \log(x)\, dx = \zeta(5) -\sum _{k=1}^{\infty }{\frac {\psi' \left( k \right) }{{k}^{3}}}\sim -0.7115661976. $$

Added: For the first one just use the power series expansions of $\operatorname{Li}_3(x)$ and $\frac{1}{1-x}$ and you end up with

$$\sum_{k=1}^{\infty}\frac{1}{k^3}\sum_{n=0}^{\infty} \int_{0}^{1} x^{k+n}\ln(x)dx=-\sum_{k=1}^{\infty}\frac{1}{k^3}\sum_{n=0}^{\infty}\frac{1}{(n+k+1)^2} $$

$$ = -\sum_{k=1}^{\infty}\frac{\psi'(k+1)}{k^3}. $$

If you manipulate the last sum, you will be able to relate it to the Euler sums as

$$ -\sum_{k=1}^{\infty}\frac{\psi'(k+1)}{k^3}= \zeta(5)-\sum_{n=1}^{\infty}\frac{H_n^{(3)}}{n^2}.$$

Note: Notice that, we are getting identities for $\zeta(5)$.

$\endgroup$
  • $\begingroup$ You could complete it , it is not that difficult! $\endgroup$ – Zaid Alyafeai Aug 13 '13 at 17:51
  • $\begingroup$ @ZaidAlyafeai: Ok. I'll be adding more material. $\endgroup$ – Mhenni Benghorbal Aug 13 '13 at 18:08
  • 1
    $\begingroup$ We can get $$\sum_{n\geq 1} \frac{H^{(2)}_n}{n^3}=\frac{1}{2}\left(\pi^2 \zeta(3) - 9 \zeta(5) \right)$$ $\endgroup$ – Zaid Alyafeai Aug 13 '13 at 21:00
  • $\begingroup$ @ZaidAlyafeai: it is not the same sum. $\endgroup$ – Mhenni Benghorbal Aug 14 '13 at 1:00
  • 1
    $\begingroup$ @MhenniBenghorbal , yes . I just wanted to point that you can prove that the integral is equal to $$\frac{1}{6}\left(2 \pi^2 \zeta(3) - 27 \zeta(5) \right)$$ using the Euler sum you derived . $\endgroup$ – Zaid Alyafeai Aug 14 '13 at 2:54
4
$\begingroup$

$\newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ $\ds{\int_{0}^{1}{{\rm Li}_{3}\pars{x}\ln\pars{x} \over 1 - x}\,\dd x: \ {\large ?}}$.

In this post it's shown, in general grounds, that: $$ \int_{0}^{1}{{\rm Li}_{q}\pars{x}\ln^{r - 1}\pars{x} \over 1 - x}\,\dd x =\pars{-1}^{r - 1}\pars{r - 1}!\bracks{\zeta\pars{r}\zeta\pars{q}% -\sum_{n = 1}^{\infty}{H_{n}^{\rm\pars{r}} \over n^{q}}} $$ where $\ds{\zeta\pars{z}}$ is the Riemann Zeta Function and $\ds{H_{n}^{\rm \pars{r}} \equiv \sum_{k = 1}^{n}{1 \over k^{\rm r}}}$ is a Generalized Harmonic Number

such that $\ds{\pars{~\mbox{with}\ q = 3\ \mbox{and}\ r = 2~}}$: $$ \int_{0}^{1}{{\rm Li}_{3}\pars{x}\ln\pars{x} \over 1 - x}\,\dd x =\sum_{n = 1}^{\infty}{H_{n}^{\rm\pars{2}} \over n^{3}} - \zeta\pars{2}\zeta\pars{3}\,,\qquad H_{n}^{\rm\pars{2}} = \sum_{k = 1}^{n}{1 \over k^{2}} $$

In a comment of this answer, the OP $\pars{\tt @Zaid\ Alfayeai}$ pointed out that $\ds{\sum_{n = 1}^{\infty}{H_{n}^{\rm\pars{2}} \over n^{3}} = 3\zeta\pars{2}\zeta\pars{3} - {9 \over 2}\,\zeta\pars{5}}$ such that

$$\color{#66f}{\large% \int_{0}^{1}{{\rm Li}_{3}\pars{x}\ln\pars{x} \over 1 - x}\,\dd x =2\zeta\pars{2}\zeta\pars{3} - {9 \over 2}\,\zeta\pars{5}} \approx {\tt -0.7115} $$

$\endgroup$
2
$\begingroup$

\begin{align} \int^1_0\frac{\log{x} \ {\rm Li}_3(x)}{1-x}{\rm d}x &=\sum^\infty_{n=1}H_n^{(3)}\int^1_0x^n\log{x} \ {\rm d}x\\ &=-\sum^\infty_{n=1}\frac{H_n^{(3)}}{(n+1)^2}\\ &=\sum^\infty_{n=1}\frac{1}{(n+1)^5}-\sum^\infty_{n=1}\frac{H_{n+1}^{(3)}}{(n+1)^2}\\ &=\zeta(5)-\underbrace{\sum^\infty_{n=1}\frac{H_{n}^{(3)}}{n^2}}_{S} \end{align} Consider $\displaystyle f(z)=\frac{\pi\cot{\pi z} \ \Psi^{(2)}(-z)}{z^2}$. We know that \begin{align}\pi\cot{\pi z}&=\frac{1}{z-n}-2\sum^\infty_{k=1}\zeta(2k)(z-n)^{2k-1}\\&\approx\frac{1}{z-n}-2\zeta(2)(z-n)\end{align} (see here for a proof) and \begin{align}\Psi^{(2)}(-z)&=\frac{2}{(z-n)^3}+\sum^\infty_{k=2}(-1)^{k}k(k-1)\left(H_n^{(k+1)}+(-1)^{k+1}\zeta(k+1)\right)(z-n)^{k-2}\\&\approx\frac{2}{(z-n)^3}+2\left(H_n^{(3)}-\zeta(3)\right)\end{align} At the positive integers, \begin{align} {\rm Res}(f,n) &=\operatorname*{Res}_{z=n}\left[\frac{2}{z^2(z-n)^4}-\frac{4\zeta(2)}{z^2(z-n)^2}+\frac{2\left(H_n^{(3)}-\zeta(3)\right)}{z^2(z-n)}\right]\\ &=-\frac{8}{n^5}+\frac{8\zeta(2)}{n^3}+\frac{2H_n^{(3)}}{n^2}-\frac{2\zeta(3)}{n^2} \end{align} At the negative integers, \begin{align} {\rm Res}(f,-n) &=\frac{\Psi^{(2)}(n)}{n^2}\\ &=\frac{2H_{n}^{(3)}}{n^2}-\frac{2\zeta(3)}{n^2}-\frac{2}{n^5} \end{align} At $z=0$, \begin{align} {\rm Res}(f,0) &=[z^1]\left(\frac{1}{z}-2\zeta(2)z\right)\left(-2\zeta(3)-12\zeta(5)z^2\right)\\ &=-12\zeta(5)+4\zeta(2)\zeta(3) \end{align} Hence \begin{align}4S&=8\zeta(5)-8\zeta(2)\zeta(3)+2\zeta(2)\zeta(3)+2\zeta(2)\zeta(3)+2\zeta(5)+12\zeta(5)-4\zeta(2)\zeta(3)\\&=22\zeta(5)-8\zeta(2)\zeta(3)\end{align} which implies $$\color{blue}{\int^1_0\frac{\log{x} \ {\rm Li}_3(x)}{1-x}}=\zeta(5)-\frac{22\zeta(5)-8\zeta(2)\zeta(3)}{4}=\color{blue}{2\zeta(2)\zeta(3)-\frac{9}{2}\zeta(5)}$$

$\endgroup$
1
$\begingroup$

\begin{align} I&=\int_0^1\frac{\operatorname{Li}_3(x)\ln x}{1-x}\ dx=\sum_{n=1}^\infty\left(H_n^{(3)}-\frac1{n^3}\right)\int_0^1x^{n-1}\ln x\ dx\\ &=\sum_{n=1}^\infty \left(H_n^{(3)}-\frac1{n^3}\right)\left(-\frac{1}{n^2}\right)=\zeta(5)-\sum_{n=1}^\infty\frac{H_n^{(3)}}{n^2}\tag{1} \end{align} lets start with the following sum \begin{align} S&=\sum_{n=1}^\infty\frac{H_n^{(2)}}{n^3}=\sum_{n=1}^\infty\frac1{n^3}\left(\zeta(2)-\sum_{k=1}^\infty\frac{1}{(n+k)^2}\right)\\ &=\zeta(2)\zeta(3)-\sum_{k=1}^\infty\left(\sum_{n=1}^\infty\frac1{n^3(n+k)^2}\right)\\ &=\zeta(2)\zeta(3)-\sum_{k=1}^\infty\left(\sum_{n=1}^\infty\left(-\frac3{k^4}\left(\frac1n-\frac1{n+k}\right)+\frac2{k^3n^2}+\frac1{k^3(n+k)^2}-\frac1{k^2n^3}\right)\right)\\ &=\zeta(2)\zeta(3)-\sum_{k=1}^\infty\left(-\frac{3H_k}{k^4}+\frac{2\zeta(2)}{k^3}+\frac1{k^3}\left(\zeta(2)-H_k^{(2)}\right)-\frac{\zeta(3)}{k^2}\right)\\ &=\zeta(2)\zeta(3)-3\sum_{k=1}^\infty\frac{H_k}{k^4}+2\zeta(2)\zeta(3)+\zeta(2)\zeta(3)-S-\zeta(2)\zeta(3)\\ 2S&=3\zeta(2)\zeta(2)-3\left(3\zeta(5)-\zeta(2)\zeta(3)\right)\\ S&=3\zeta(2)\zeta(3)-\frac92\zeta(5) \end{align} using the well known formula $$\sum_{n=1}^\infty\frac{H_n^{(a)}}{n^b}+\sum_{n=1}^\infty\frac{H_n^{(b)}}{n^a}=\zeta(a)\zeta(b)+\zeta(a+b)$$ therefore $$\sum_{n=1}^\infty\frac{H_n^{(3)}}{n^2}=\zeta(2)\zeta(3)+\zeta(5)-\sum_{n=1}^\infty\frac{H_n^{(2)}}{n^3}=\frac{11}{2}\zeta(5)-2\zeta(2)\zeta(3)\tag{2}$$ plugging $(2)$ in $(1)$, we get $$I=2\zeta(2)\zeta(3)-\frac{9}{2}\zeta(5)$$

$\endgroup$
0
$\begingroup$

$$\int_0^1\ln(x)\frac{Li_1(x)}{1-x}dx=-\zeta(3)$$ $$\int_0^1\ln(x)\frac{Li_2(x)}{1-x}dx=-\frac{3}{10}\zeta^2(2)$$ The same method may work for the present case. (To be continued.)

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.